The predictability of the ringgit Malaysia against the United States dollar exchange rate - Sook Ching Kok; Saizal Pinjaman; Caroline Geetha (RSIS International, 2025)
This study investigates the validity of the weak-form Efficient Market Hypothesis (EMH) for the Ringgit Malaysia (RM) against the United States Dollar (USD) exchange rate by examining whether historical price movements possess predictive power over future values. Using annual exchange rate data from 1960 to 2024, the analysis is segmented into three distinct periods: pre-COVID-19 (1960–2019), during-COVID-19 (2020–2021), and post-COVID-19 (2022–2024), to account for structural shifts and macroeconomic shocks. Three statistical methods were employed: the Runs test for randomness, the Variance Ratio test for random walk properties, and the Ljung-Box Q test for serial correlation. The results reveal that the RM/USD exchange rate exhibited significant predictability and informational inefficiency in the pre-COVID period, likely due to the historical use of managed exchange rate regimes and limited market liberalization. In contrast, the post-COVID period shows strong support for weak-form efficiency, indicating improved market maturity, transparency, and responsiveness to information. These findings highlight that market efficiency in Malaysia’s foreign exchange market is not static, but evolves with changes in institutional quality, policy frameworks, and global economic conditions. The study contributes to the literature on emerging market efficiency and has implications for investors, policymakers, and currency risk management strategies in a post-pandemic financial landscape.